Inculturazione e sfida educativa - Cristiano Casalini (Firenze University Press, 2013)
"Inculturation" is a term introduced in theology by the General Congregation of the Society of Jesus. Fr. Pedro Arrupe S.J. wrote a well-known letter on this topic, gaining for the term "inculturation" a great fortune in Catholic culture and education. Yet, its meaning and importance are usually neglected by educational theorists, who prefer to deal with the concept of "intercultural education". But, even if several catholic theologists have more recently stated that the concept of interculture is more fertile than that of inculturation, this paper aims at demonstrating the cultural differences between the two concepts and at settling a theo- retical framework for an education based on inculturation.